KONTRIBUSI GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI GURU TERHADAP KINERJA GURU SDN SEKECAMATAN KUBU KABUPATEN ROKAN HILIR - Sri Wahyuni; Isjoni; Azhar (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Teachers are one of the resource elements that determine success in education at school because teachers as a human elements are very close to students in daily education at school. The Ministry of Education and Culture states that teachers are human resources who can utilize other factors to create a quality teaching and learning process and become the main factor that determines the quality of education. Therefore, educators (teachers) must be able toimprove performance in carrying out their duties because education in the future requires professional skills of quality education. Thus, the performance of professional teachers can be a breath of fresh air for success in the future educational context. The background of the research problem in this article is derived from the teachers who teach in class are still teaching based on their past experiences from time to time so they perceive mastering then material out of their mind and do not prefer to change new things including learning methods, use of media, assessment systems that are poorly understood and teaching. by rote or without prior teaching preparation. While the results of interviews conducted by researchers with teachers indicated that the principal has not implemented the leadership function optimally to lead his subordinates. In addition, the phenomena related to problems that occurred regarding teacher performance that can be identified were 1) the ability of teachers to develop syllabus and lesson plans (RPP) was not optimal so it produced a less attractive learning atmosphere,2) classroom management was still lacking so that a conducive atmosphere in the classroom and a fun learning process has not been created, 3) the teacher has not been maximal in utilizing the media so that the results in conveying messages (subject matter) to students were not optimal, and 4) the teacher did not vary the learning methods so students felt boredom while teaching and learning activities. Above all, the importance of teachers’ performance in participating in teaching and learning activities is necessary for teachers to increase their abilities and competencies in terms of developing syllabus and lesson plans (RPP), managing classes, and good in using media and learning methods. Based on the background, several research problems could be formulated, they are 1) does leadership style contribute to a teacher’s performance? 2) does motivation contribute to a teacher’s performance? and 3) do leadership style and motivation contribute to performance? The purpose of the research was to analyze the contribution of leadership style to teacher’s performance, to analyze thecontribution of motivation to teacher’s performance, and to analyze the contribution of leadership style and motivation to teacher’s performance. The type of research was descriptive quantitative research. The data collection technique used was a questionnaire involving 129 respondents from 98 teachers of SDN Kubu Districts in Rokan Hilir Regency who wererandomly selected as samples by using the Slovin formula. The research method used was for the respondents who gave responses to the questionnaire in the form of a Likert scale. Analysis of the data used was descriptive and inferential statistics. Based on data analysis, it was found that leadership style contributed to a teacher’s performance. The better the leadership style was provided it would affect the more effective teacher performance. It means that leadership style was an important variable to be considered in order to increase the teacher’s performance. Motivation contributed to teacher performance. The higher the teacher's motivation was described the high ethic working it would support a better teacher performance. Hence, teacher motivation was an important variable to be considered to improve teacher performance. And the leadership style and teacher’s motivation contributed to the teacher’s performance.